AN IMPORTANT ROLE OF INFORMATION COMMUNICATION TECHNOLOGIES ACTIVELY USED IN THE TEACHING OF FOREIGN LANGUAGES FOR STUDENTS OF THE NON-PHILOSOPHICAL EDUCATION COURSE (American Journal of Interdisciplinary Research and Development, 2023)
Knowledge of languages in socio-political, agricultural, and other fields of Uzbekistan's development becomes a necessary component of a person's personal and professional life, and the requirements of government and society for the results of linguistic preparation should be expressed in their ability to use the languages studied in real cultural dialogue